(untitled) (CIPEEX, 2026)
Active transportation, such as walking or cycling daily, has gained relevance in the last decade as a strategy to promote physical activity and improve public health. Scientific evidence indicates that active mobility not only reduces sedentary lifestyles but also has positive impacts on physical, mental, and metabolic health indicators, in addition to promoting environmental and urban benefits. The study “Health indicators related to urban mobility by bicycle: a cross-sectional study with company employees in the city of Anápolis” had the overall objective of assessing the impacts of active mobility on the health and well-being of working adults. The specific objectives were: to compare health and well-being variables between practitioners and non-practitioners of active mobility; to analyze the relationship between distance traveled and perception of well-being; and to identify the main obstacles to its adoption. This is a cross-sectional study, conducted in accordance with STROBE guidelines. The population consisted of adult workers in the city of Anápolis, Brazil, divided into an intervention group (active commuting) and a control group (motorized transport). Participants in the intervention group are expected to have a lower body mass index (BMI), better metabolic profile, and greater functional capacity. In the psychological field, an improvement in sleep quality, reduced stress, and greater perception of well-being are expected. Active mobility is a strategic alternative to promote integral health, strengthen emotional well-being, and contribute to more sustainable and inclusive cities.